Toward Continuous Innovation in Teaching: Reflective Practice on English Teaching of Indonesian and the Philippine Teachers - Mauly Halwat Hikmat; Regina F. Santos; Suharyanto Suharyanto; Ainurvely Gehandiatie Maudy; Khamlan Phommavongsa (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
The ability to reflect on a teacher is critical as part of his/her self-agency to become a professional teacher. This research aimed to compare Indonesian and Philippine teachers' reflection practice on English teaching. The research was focused on 1) the questions teachers of both countries ask as the reflection in their Teaching, 2) their perceptions about their reflection of their teaching practice, and 3) their follow-up on the reflection. The participants in this study were 16 English teachers in the Philippines and 30 teachers in Indonesia. Data were collected through questionnaires, interviews, and observations and analyzed through inductive analysis techniques. The study revealed a slight difference in the focus of the reflective questions asked by the Philippine and Indonesian teachers. Indonesian teachers focus more on the students’ learning, while Philippine teachers do self-reflection. However, both countries' teachers thought reflection was important for their professional development. The structured reflection practice will likely help teachers of both countries plan their professional development and innovation in teaching practice.